Role of “Dirilis Ertugrul” in Creating Awareness and Understanding of Islam Among Pakistani Youth - Dr. Zaeem Yasin; Naveed Iqbal; Hareema Tariq; Maha Fareed; Ilsa Islam (Journal of Management Practices, Humanities and Social Sciences, 2021)
This study investigated the “Role of Dirilis Ertugrul in Creating Awareness and Understanding of Islam Among Pakistani Youth” through both qualitative and quantitative research methods, i.e., Focus Group and Survey Method. The researcher has applied the Play Theory of mass media to support the study. Youngsters of Lahore are selected as a population with the help of the purposive sampling technique. The Chi-square test is applied for hypothesis testing. Hypothesis “Dirilis Ertugrul reinforces Islamic ideologies and Islamic values or norms on the youth of Pakistan” is accepted. The study finding revealed that the majority of the youngsters agreed that Dirilis Ertugrul connects people more with Islam, its history, and culture. The series shows truly Islamic heroes, their history and, culture and also educates masses regarding Islam. Dirilis Ertugrul engaged Muslims, especially youth, into being passionate about their Muslim faith and identity. The study also identifies that Dirilis Ertugrul raised awareness and understanding of Islam in Pakistani youth. They are now more aware of Islam, its teachings, its history, its culture, and its ethics. They are proud of their religion and religious heroes. The majority of the youngsters agreed that this type of drama series should be produced by the Muslim world not only to show their true religion to the world but also to educate their people. Media has always played a crucial role in shaping our society. Nowadays, dramas influence so many people’s behavior. It can influence, manipulate, persuade and pressurize society and even control people negatively or positively, mentally, physically, or emotionally. In Pakistan, most of the Drama narratives revolve around family drama, extramarital affairs, love triangle, second marriage, domestic violence, and so on. But one drama series which storm around the country and broke all records of viewership in Pakistan is the Turkish historical drama series Dirilis Ertugrul.